Ekosocializem kot povezava družbenosti in sonaravnosti - Kirn, Andrej (Varstvo narave, 2016)
Eco-socialism is becoming a feasible alternative. It has to continue to deepen and widen socioecological changes that started in neoliberal capitalism due to pressure stemming from social and environmental movements. Eco-socialism means a new relationship between people and a new attitude of man towards nature. It is hoped that it can help avoid socioecological disaster.
Keywords: družbena gibanja; družbenoekološki obrat; ecological crisis; eco-socialism; ekokapitalizem; ekološka kriza; ekosocializem; environmental movements; neoliberalism; neoliberalizem; okoljska gibanja; sco-capitalism; social movements; socialism; socializem; sociological turn; system compatible alternatives; znotrajsistemske alternative